Automated Software Testing Using Program Analysis - Godefroid, Patrice; Halleux, Jonathan "Peli" de; Nori, Aditya; Rajamani, Sriram; Schulte, Wolfram; Tillmann, Nikolai; Levin, Michael Y. (IEEE Software, Special Issue on Software Development Tools, 2008)
During the last ten years, code inspection for standard programming errors has largely been automated with static code analysis. During the next ten years, we believe we will see similar progress in automating testing, and specifically test generation, thanks to advances in program analysis, efficient constraint solvers and powerful computers. We present an overview of several related projects currently under way at Microsoft.